Biomass-modulated fire dynamics during the last glacial-interglacial transition at the Central Pyrenees (Spain) - Gil-Romera, Graciela; González-Sampériz, Penélope; Lasheras-Álvarez, Laura; Sevilla-Callejo, Miguel; Moreno, Ana; Valero-Garcés, Blas; López-Merino, Lourdes; Carrión, José S; Pérez Sanz, Ana; Aranbarri, Josu; García-Prieto Fronce, Eduardo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2014)
Understanding long-term fire ecology is essential for current day interpretation of ecosystem fire responses. However palaeoecology of fire is still poorly understood, especially at high-altitude mountain environments, despite the fact that these are fire-sensitive ecosystems and their resilience might be affected by changing fire regimes. We reconstruct wildfire occurrence since the Lateglacial (14.7calka BP) to the Mid-Holocene (6calka BP) and investigate the climate–fuel–fire relationships in a sedimentary sequence located at the treeline in the Central Spanish Pyrenees. Pollen, macro- and micro-charcoal were analysed for the identification of fire events (FE) in order to detect vegetation post-fire response and to define biomass–fire interactions. mean fire intervals (mfi) reduced since the Lateglacial, peaking at 9–7.7calka BP while from 7.7 to 6calka BP no fire is recorded. We hypothesise that Early Holocene maximum summer insolation, as climate forcing, and mesophyte forest expansion, as a fuel-creating factor, were responsible for accelerating fire occurrence in the Central Pyrenees treeline. We also found that fire had long-lasting negative effects on most of the treeline plant communities and that forest contraction from 7.7calka BP is likely linked to the ecosystem's threshold response to high fire frequencies.
Keywords: Fire history; historical biogeography; iberian peninsula; l Palaeoecology; Lateglacia; quaternary

1200 years of decadal-scale variability of Mediterranean vegetation and climate at Pantelleria Island, Italy - Calò, Camilla; Henne, Paul D.; Eugster, Patricia; van Leeuwen, Jacqueline; Gilli, Adrian; Hamann, Yvonne; La Mantia, Tommaso; Pasta, Salvatore; Vescovi, Elisa; Tinner, Willy (HOLOCENE, 2013)
A new sedimentary sequence from Lago di Venere on Pantelleria Island, located in the Strait of Sicily between Tunisia and Sicily was recovered. The lake is located in the coastal infra-Mediterranean vegetation belt at 2 m a.s.l. Pollen, charcoal and sedimentological analyses are used to explore linkages among vegetation, fire and climate at a decadal scale over the past 1200 years. A dry period from ad 800 to 1000 that corresponds to the Medieval Warm Period' (WMP) is inferred from sedimentological analysis. The high content of carbonate recorded in this period suggests a dry phase, when the ratio of evaporation/precipitation was high. During this period the island was dominated by thermophilous and drought-tolerant taxa, such as Quercus ilex, Olea, Pistacia and Juniperus. A marked shift in the sediment properties is recorded at ad 1000, when carbonate content became very low suggesting wetter conditions until ad 1850-1900. Broadly, this period coincides with the Little Ice Age' (LIA), which was characterized by wetter and colder conditions in Europe. During this time rather mesic conifers (i.e. Pinus pinaster), shrubs and herbs (e.g. Erica arborea and Selaginella denticulata) expanded, whereas more drought-adapted species (e.g. Q. ilex) declined. Charcoal data suggest enhanced fire activity during the LIA probably as a consequence of anthropogenic burning and/or more flammable fuel (e.g. resinous Pinus biomass). The last century was characterized by a shift to high carbonate content, indicating a change towards drier conditions, and re-expansion of Q. ilex and Olea. The post-LIA warming is in agreement with historical documents and meteorological time series. Vegetation dynamics were co-determined by agricultural activities on the island. Anthropogenic indicators (e.g. Cerealia-type, Sporormiella) reveal the importance of crops and grazing on the island. Our pollen data suggest that extensive logging caused the local extinction of deciduous Quercus pubescens around ad1750.
The following values have no corresponding Zotero field: pub-location: 1 OLIVERS YARD, 55 CITY ROAD, LONDON EC1Y 1SP, ENGLAND publisher: SAGE PUBLICATIONS LTD
Keywords: '"Little Ice Age' (LIA); 'Medieval Warm Period' (MWP); central Mediterranean; Fire history; Pinus pinaster; Quercus ilex; Quercus pubescens; vegetation history

Vegetation, fire, climate and human disturbance history in the southwestern Mediterranean area during the late Holocene - Jiménez-Moreno, Gonzalo; García-Alix, Antonio; Hernández-Corbalán, María Dolores; Anderson, R. Scott; Delgado-Huertas, Antonio (Quaternary Research, 2012)
Detailed pollen, charcoal, isotope and magnetic susceptibility data from an alpine lake sediment core from Sierra Nevada, southern Spain record changes in vegetation, ﬁre history and lake sedimentation since ca. 4100 cal yr BP. The proxies studied record an arid period from ca. 3800 to 3100 cal yr BP characterized by more xerophytic vegetation and lower lake levels. A humid period is recorded between ca. 3100 and 1850 cal yr BP, which occurred in two steps: (1) an increase in evergreen Quercus between 3100 and 2500 cal yr BP, indicating milder conditions than previously and (2) an increase in deciduous Quercus and higher lake levels, between ca. 2500 and 1850 cal yr BP, indicating a further increase in humidity and reduction in seasonal contrast. Humid maxima occurred during the Roman Humid Period, previously identiﬁed in other studies in the Mediterranean region. Intensiﬁed ﬁre activity at this time could be related to an increase in fuel load and/or in human disturbance. An arid period subsequently occurred between 1850 and 650 cal yr BP, though a decrease in Quercus and an increase in xerophytes. The alternation of persistent North Atlantic Oscillation modes probably played an important role in controlling these humid–arid cycles
The following values have no corresponding Zotero field: publisher: University of Washington
Keywords: climate; Fire history; Late Holocene; Roman Humid Period; Sierra Nevada; southern Spain

Response of broadleaved evergreen Mediterranean forest vegetation to fire disturbance during the Holocene: insights from the peri-Adriatic region - Colombaroli, Daniele; Tinner, Willy; van Leeuwen, Jacqueline; Noti, Roland; Vescovi, Elisa; Vannière, Boris; Magny, Michel; Schmidt, Roland; Bugmann, Harald (Journal of Biogeography, 2009)
Aim To test whether fire contributed to the expansion and compositional change of evergreen forests in the Mediterranean region during the Holocene. Location The peri-Adriatic region, encompassing the Italian peninsula, Sicily and the western and southern Balkans between latitudes 46° and 37° N. Methods New high-resolution pollen and microscopic charcoal data from Lago dell’Accesa (Tuscany, Italy) were used to estimate the response of the evergreen oak, Quercus ilex L., to fire during its expansion phase at 8500 cal. yr bp. The data were compared with the pollen and charcoal series from other Mediterranean sites (Lago di Massaciuccoli in Tuscany, Malo Jezero in Croatia, Biviere di Gela in Sicily) and analysed using numerical techniques (redundancy analysis, detrended canonical correspondence analysis) to identify long-term fire–vegetation linkages and the degree of compositional change. Results Microscopic charcoal and pollen of evergreen oaks were negatively correlated during the period of quasi-natural fire regime (Mesolithic, 10,000–8000 cal. yr bp). In addition, there was no such positive correlation during periods when the fire regime was potentially more influenced by people (Neolithic–Bronze Age, 8000–3000 cal. yr bp). Compared with inland sites, coastal sites that are currently located at a distinct ecotone showed more compositional change. Main conclusions The analyses suggest that climatic change, without an additional effect of fire regimes, favoured the expansion and compositional change of evergreen forests across the peri-Adriatic region. Strikingly different patterns occurred along a north–south gradient. In the north (Tuscany and Croatia, meso-Mediterranean belt), Q. ilex replaced deciduous forests when conditions became drier; in the south (Sicily, thermo-Mediterranean belt) the species replaced maquis or steppe vegetation when climatic conditions became moister. We conclude that the projected increase in fire activity may lead to the loss of most of the remaining relict forests of Q. ilex in southern Europe.
Keywords: Compositional change; cross-correlations; Fire history; Mediterranean vegetation; microscopic charcoal analysis; Pollen analysis; Quercus ilex; redundancy analysis; species diversity

Response of broadleaved evergreen Mediterranean forest vegetation to fire disturbance during the Holocene: insights from the peri-Adriatic region - Colombaroli, Daniele; Tinner, Willy; van Leeuwen, Jacqueline; Noti, Roland; Vescovi, Elisa; Vannière, Boris; Magny, Michel; Schmidt, Roland; Bugmann, Harald (Journal of Biogeography, 2009)
Aim To test whether fire contributed to the expansion and compositional change of evergreen forests in the Mediterranean region during the Holocene. Location The peri-Adriatic region, encompassing the Italian peninsula, Sicily and the western and southern Balkans between latitudes 46° and 37° N. Methods New high-resolution pollen and microscopic charcoal data from Lago dell’Accesa (Tuscany, Italy) were used to estimate the response of the evergreen oak, Quercus ilex L., to fire during its expansion phase at 8500 cal. yr bp. The data were compared with the pollen and charcoal series from other Mediterranean sites (Lago di Massaciuccoli in Tuscany, Malo Jezero in Croatia, Biviere di Gela in Sicily) and analysed using numerical techniques (redundancy analysis, detrended canonical correspondence analysis) to identify long-term fire–vegetation linkages and the degree of compositional change. Results Microscopic charcoal and pollen of evergreen oaks were negatively correlated during the period of quasi-natural fire regime (Mesolithic, 10,000–8000 cal. yr bp). In addition, there was no such positive correlation during periods when the fire regime was potentially more influenced by people (Neolithic–Bronze Age, 8000–3000 cal. yr bp). Compared with inland sites, coastal sites that are currently located at a distinct ecotone showed more compositional change. Main conclusions The analyses suggest that climatic change, without an additional effect of fire regimes, favoured the expansion and compositional change of evergreen forests across the peri-Adriatic region. Strikingly different patterns occurred along a north–south gradient. In the north (Tuscany and Croatia, meso-Mediterranean belt), Q. ilex replaced deciduous forests when conditions became drier; in the south (Sicily, thermo-Mediterranean belt) the species replaced maquis or steppe vegetation when climatic conditions became moister. We conclude that the projected increase in fire activity may lead to the loss of most of the remaining relict forests of Q. ilex in southern Europe.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Compositional change; cross-correlations; Fire history; Mediterranean vegetation; microscopic charcoal analysis; Pollen analysis; Quercus ilex; redundancy analysis; species diversity

Fire-vegetation interactions during the Mesolithic-Neolithic transition at Lago dell'Accesa, Tuscany, Italy - Colombaroli, Daniele; Vannière, Boris; Emmanuel, Chapron; Magny, Michel; Tinner, Willy (HOLOCENE, 2008)
A new core from the centre of Lago dell'Accesa (Tuscany, Italy) was sampled for pollen and charcoal analyses to provide a high-resolution sequence from 8400 to 7000 cal. yr BP. We combined series of microscopic charcoal, macroscopic charcoal and pollen to address the response of vegetation to fire at different spatial scales. Before 7900 cal. yr BP, broadleaved evergreen forests of Quercus ilex were the most important vegetational type in the area of Lago dell'Accesa. The subsequent decline of Q. ilex occurred when human-induced fires increased at the Mesolithic/Neolithic transition (c. 8000 cal. yr BP). Cross-correlation analyses show that fire was a key factor for vegetational change. Higher fire incidence affected the forest composition, converting evergreen forests to high-diversity open, partly deciduous forests and shrubby communities. The correlation is more pronounced at a local scale (macroscopic charcoal), whereas at a regional scale (microscopic charcoal) the vegetation followed the fire intervals with a more marked time lag (10-100 years). Climatic change, such as wetter periods inferred from lake levels, may have directly influenced the vegetational change, exacerbating the effect of human impact. Our study suggests that the disruption of evergreen broadleaved forests occurred when mean fire interval reached values as high as those of today's highly disturbed Mediterranean ecosystems. Hence broadleaved evergreen forests may not be as fire-resilient as assumed according to modern ecological paradigms. In view of the projected increase in fire frequency as a consequence of global warming, the present relict forests of Quercus ilex will be strongly affected.
Keywords: climate change; Fire ecology; Fire history; Holocene; Italy; macroscopic charcoal; Mediterranean vegetation; mesolithic; microscopic charcoal; Neolithic; Quercus ilex; tuscany

Fire-vegetation interactions during the Mesolithic-Neolithic transition at Lago dell'Accesa, Tuscany, Italy - Colombaroli, Daniele; Vannière, Boris; Emmanuel, Chapron; Magny, Michel; Tinner, Willy (HOLOCENE, 2008)
A new core from the centre of Lago dell'Accesa (Tuscany, Italy) was sampled for pollen and charcoal analyses to provide a high-resolution sequence from 8400 to 7000 cal. yr BP. We combined series of microscopic charcoal, macroscopic charcoal and pollen to address the response of vegetation to fire at different spatial scales. Before 7900 cal. yr BP, broadleaved evergreen forests of Quercus ilex were the most important vegetational type in the area of Lago dell'Accesa. The subsequent decline of Q. ilex occurred when human-induced fires increased at the Mesolithic/Neolithic transition (c. 8000 cal. yr BP). Cross-correlation analyses show that fire was a key factor for vegetational change. Higher fire incidence affected the forest composition, converting evergreen forests to high-diversity open, partly deciduous forests and shrubby communities. The correlation is more pronounced at a local scale (macroscopic charcoal), whereas at a regional scale (microscopic charcoal) the vegetation followed the fire intervals with a more marked time lag (10-100 years). Climatic change, such as wetter periods inferred from lake levels, may have directly influenced the vegetational change, exacerbating the effect of human impact. Our study suggests that the disruption of evergreen broadleaved forests occurred when mean fire interval reached values as high as those of today's highly disturbed Mediterranean ecosystems. Hence broadleaved evergreen forests may not be as fire-resilient as assumed according to modern ecological paradigms. In view of the projected increase in fire frequency as a consequence of global warming, the present relict forests of Quercus ilex will be strongly affected.
The following values have no corresponding Zotero field: pub-location: 1 OLIVERS YARD, 55 CITY ROAD, LONDON EC1Y 1SP, ENGLAND publisher: SAGE PUBLICATIONS LTD
Keywords: climate change; Fire ecology; Fire history; Holocene; Italy; macroscopic charcoal; Mediterranean vegetation; mesolithic; microscopic charcoal; Neolithic; Quercus ilex; tuscany